Expenditure and Nutritional Impact of Banning the Promotion of Foods High in Fat, Sugar and Salt in Scotland - Revoredo-Giha, Cesar; McNamee, Paul; Norwood, Patricia; Akaichi, Faical; Dogbe, Wisdom (Frontiers in Nutrition, 2022)
The purpose of the paper is to provide an ex-ante evaluation of restricting price promotions for discretionary foods (e.g., such as confectionary, crisps, biscuits, sweet and savoury snacks, cakes) in Scotland. The methodology consisted of the estimation of demand systems by socioeconomic groups (i.e., lifestage and income groups) for 19 food groups using a highly product disaggregated dataset. These results were used to simulate scenarios consisting of eliminating price promotions on the discretionary food products for the entire sample and by group and analysing nutritional results. The results indicated a net impact of reducing energy by 651 kcal per capita per week. Similar results were found for macro nutrients. There were some significant differences across different income and lifestage groups, with kcal energy reductions being significantly greater amongst household with lower income, and in households where respondents were aged 45 years or over. The analysis concluded that restrictions on the promotion of foods considered to be high in saturated fat, sugar, or salt (HFSS) are seen as one measure to improve the overall nutritional quality of foods consumed. Results indicate that restricting promotions has the potential to reduce the number of calories, sugar, saturated fats and sodium for most food groups.